Weed Management in Small Grains Harvested for Grain - Jason Ferrell; Gregory MacDonald; Pratap Devkota (EDIS)
Successful weed control in small grains involves using good management practices in all phases of production. In Florida, winter weeds compete with small grains for moisture, nutrients, and light, with the greatest amount of competition occurring during the first six to eight weeks after planting. Weeds also cause harvest problems the following spring when the small grain is mature. This 4-page publication discusses crop competition, knowing your weeds, and chemical control. Written by J. A. Ferrell, G. E. MacDonald, and P. Devkota, and published by the UF/IFAS Agronomy Department, revised May 2020.